Determinants of The Use of The Flip Application on UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan Students - Hutagalung, Muhammad Wandisyah R; Elce, Furkan; Lestari, Sry (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
Islamic banking study program students who already know the admin fee-free application, but only a few use the admin fee-free application. Even though it is easy and useful, only some students use the flip application, and some students still believe in doing transactions using the flip applicationfeel more comfortable doing transactions directly to the ATM. The formulation of the problem in this study is whether there is a partial and simultaneous effect of ease, benefit, and trust in the decision to use the flip application for students of the Islamic Banking study program at Syekh Ali Hasan Ahmad Addary State Islamic University Padangsidimpuan. Objective the research was to determine the effect of convenience, usefulness, trust partially and simultaneously on students of the Islamic Banking study program at the State Islamic University of Syekh Ali Hasan Ahmad Addary Padangsidimpuan. The theory in this study uses the factors that influence decisions, namely: perceived usefulness, perceived ease of use, attitude, and behavioral intention. This research is a quantitative research, the data source used is primary data and data collection using questionnaires and documentation techniques.The research sample is 89 samples with techniques purposive sampling. The data analysis techniques used in this study are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, coefficient of determination test (R 2 ), partial test (t test), and simultaneous significant test (F test), multiple linear analysis. The results of the study show that partially the variables of convenience, usefulness and trust influence the decision to use the flip application in students of the Islamic Banking study program at Syekh Ali Hasan Ahmad Addary Padangsidimpuan State Islamic University. Simultaneously the variables of convenience, usefulness, and trust influence the decision to use the flip application in students of the Islamic Banking study program at the State Islamic University of Syekh Ali Hasan Ahmad Addary Padangsidimpuan.